A Personalized Electronic Tattoo for Healthcare Realized by On‐the‐Spot Assembly of an Intrinsically Conductive and Durable Liquid‐Metal Composite (Adv. Mater. 32/2022). Issue 32 (9th August 2022) - Lee, Gun‐Hee; Woo, Heejin; Yoon, Chanwoong; Yang, Congqi; Bae, Jae‐Young; Kim, Wonsik; Lee, Do Hoon; Kang, Heemin; Han, Seungmin; Kang, Seung‐Kyun; Park, Seongjun; Kim, Hyung‐Ryong; et al.
Abstract : E‐Tattoos In article number 2204159, Hyung‐Ryong Kim, Jae‐Woong Jeong, Steve Park, and co‐workers introduce a new class of e‐tattoo that can be implemented on‐the‐fly according to users' demands. To realize intimate, compact, and rapid assembly of intrinsically conductive and durable EGaIn composites, ethanol‐based ink is developed. Demonstrations of wearable bioelectronics confirm the validity of the e‐tattoo in healthcare.